Absorption Time and Temperature Effects on The Physical Chemical Properties of Refined Used Cooking Oil Using Bentonite and Carbon Bagasse Adsorbents: Pengaruh Temperature dan Waktu Absorpsi Terhadap Properti Fisik dan Kimia dari Minyak Goreng Bekas yang Dimurnikan Menggunakan Adsorben Bentonit dan Karbon Ampas Tebu - Adhiksana, Arief; Febriyana, Qobid; Wahyudi, Wahyudi; Irwan, Muhammad; Tahir, Ramli; Fitriyana, Fitriyana; Kusyanto, Kusyanto; Oko, Syarifuddin (Fakultas Teknik, Universitas Brawijaya, 2024)
Bentonite and carbon bagasse adsorbents are used to study the effects of temperature and absorption time on the physico-chemical properties of refined used cooking oil. Any extended use of outdated cooking oil will have an impact on the body's health since it causes fat cells to accumulate in various vital organs. Used cooking oil can be cleaned by using adsorbents like bentonite, bagasse, and activated carbon. This study investigated the effects of temperature and adsorption period on the purification results of used cooking oil using activated carbon adsorbents comprised of bagasse and bentonite. In this study, a factorial group randomised design was used. First, there is a 1:1 adsorbent to substrate ratio. Secondly, there are four adsorption temperature levels: 30°C, 60°C, 90°C, and 120°C. The third factor is adsorption time, which are: 30, 60, 90, and 120 minutes. Counting the quantity of acids, peroxides, and free fatty acids was one method of data analysis. The best results are obtained when used cooking oil is refined using activated carbon, bagasse, and bentonite at 120°C for 90 minutes of adsorption. The result is an acid number of 0.913, a peroxide number of 2.532, and a free fatty acid content of 0.459%.